Developing and validating an ethnomathematics-based learning module from the traditional house and accessories of the Dayak Bumi Segandu Indramayu Tribe for junior high school students - Nandang Nandang; Mochammad Taufan; Mellawaty Mellawaty; Runisah Runisah; Ratna Sri Rahayu; Ronaldo Rafael Olivero-Acuña; Jenisus O. Dejarlo (Nashir Al-Kutub Indonesia, 2026)
Ethnomathematics research has documented mathematical concepts embedded in various Indonesian cultural artifacts; however, few studies have transformed these findings into validated instructional materials, and the traditional houses and accessories of the Dayak Bumi Segandu Indramayu community remain unexplored in mathematics education literature. This study addressed this gap by combining an ethnographic exploration with the ADDIE development model to design and validate an ethnomathematics-based learning module on three-dimensional geometry for seventh-grade junior high school students. The research was conducted at Padepokan Nyi Ratu Kembar Jaya, Krimun Village, Indramayu Regency. Data were collected through observations, interviews, and documentation involving four purposively selected participants representing the community leadership and members. Qualitative data were analyzed using coding, data reduction, data display, and conclusion drawing assisted by ATLAS.ti 8. The exploration identified mathematical concepts embedded in traditional houses and cultural accessories, including lines, angles, plane figures, and solid figures, which were integrated into the module. Validation by two mathematics education experts yielded an average score of 72.8% (Good), indicating satisfactory conceptual and pedagogical quality, although improvements were recommended for language clarity. Practicality evaluation by two mathematics teachers produced an average score of 95.5% (Strongly Agree), demonstrating high classroom usability. These findings indicate that the cultural heritage of the Dayak Bumi Segandu Indramayu community can be systematically transformed into a valid and practical mathematics learning resource while contributing to the preservation of local knowledge through school mathematics.